The Role of Leadership in Dayah Development in the Technological Era - Saputra, Rizky Azhari (UIN Sjech M. Djamil Djambek Bukittinggi, 2023)
This research aims to examine Dayah's development through the role of leadership with programs that are able to respond to every development of the times. The research location is Dayah Darul Aman Tungkop Aceh Besar, a branch of Dayah Besar and one of the oldest Dayah in Aceh province, Dayah Darul Ulum Abu Lung Ie. The researcher used a qualitative research method with a case study type of research. Then the theory used by researchers is modernity theory with an emphasis on agencies. The focus of this research is the role of leaders in developing technology-based Dayah Darul Aman. The results of this research are how the development of Dayah Darul Aman is ready to respond to modernity as a form of technology-based progress, then also the role of leaders who are very influential in the development of Dayah Darul Aman. Starting with implementing the Dayah Salafiyah system, building a residential mosque within the Dayah complex, forming a foundation, opening a school program which makes the Dayah system a combination of the Dayah Salafiyah and integrated Dayah systems. This cannot be separated from the thoughts, ideas and role of the founder and first leader of Dayah who was open to the progress of the times and was not rigid about change while still maintaining religious foundations. Making Dayah Darul Aman continue to be in demand and able to respond to every technology-based advancement of the times.